Association Between Plasma Beta-endorphin and WOMAC Score in Female Patients with Knee Osteoarthritis - Hori Hariyanto; John Butar Butar; Gatot Susilo Lawrence; FX Budhianto Suhadi; Andi Husni Tanra (The Prodia Education and Research Institute (PERI), 2012)
BACKGROUND: β-endorphin plays a role in the descending pain control in the central nervous system. Central sensitization may be involved in the generating and maintenance of osteoarthritis (OA) pain. However, the correlation between β-endorphin and pain severity in OA has shown conflicting results. The aim of this study was to investigate the association between plasma β-endorphin and the severity of the disease. METHODS: This study was an observational cross-sectional study carried out on 60 female subjects with knee OA who fulfilled the inclusion criteria. Plasma β-endorphin was measured by a commercial enzyme-linked immunosorbent assay (ELISA) kit. Osteoarthritis knees were classified by the Kellegren-Lawrence (KL) grading (1-4) criteria. The Western Ontario McMaster University Osteoarthritis (WOMAC) scoring method was used to assess self-reported physical function, pain and stiffness. RESULTS: The mean of the participants' ages was 58 years old, ranging from 42 to 83 years. Overall, more than 70% of the participants were overweight with a mean of body mass index (BMI) of 27.59. More than 54% of the participants were diagnosed of having KL grading 3 or 4. Plasma β-endorphin was correlated inversely with the WOMAC subscale of stiffness (r=-0.286, p=0.0311), but no correlation was noted with the WOMAC subscale of pain and physical activity. There was no significant difference of the mean of plasma β-endorphin among the KL gradings. CONCLUSIONS: Plasma β-endorphin is associated with better WOMAC total score and stiffness subscale, but not associated with KL grading of OA. KEYWORDS: knee osteoarthritis, female, β-endorphin, WOMAC, Kellgren-Lawrence